Distribution of zakāt to non-muslims in the category of Al-Mu’allafah Qulūbuhum and its application in modern time - Hasan, Aznan; Mahadi, Nur Farhah; Mohd Noor, Azman; Zakariyah, Habeebullah; Ali, Mohammad Mahbubi (IIUM Institute of Islamic Banking and Finance, 2025)
This study undertakes a critical analysis of scholarly discourse surrounding the disbursement of zakāt to non-Muslims categorized as al-Mu’allafah Qulūbuhum (those whose hearts are reconciled). It comparatively examines diverse interpretations from both classical and contemporary fuqahā’. By doing so, the research aims to illuminate the contemporary applications of zakāt disbursement to non-Muslims within the Malaysian context. This study employs an exploratory qualitative approach to comprehensively review the diverse perspectives of jurists across the four principal Sunni madhāhib: the Ḥanafiyyah, Mālikiyyah, Shāfiʽīyah, and Ḥanbaliyyah schools, contemporary fiqh al-wāqiʽ perspectives and their application within Malaysian context. This study relies on secondary data derived from a comprehensive review of relevant academic publications, including classical and contemporary manuscripts, journal articles, and research papers, as well as professional resources such as websites, official documents, and reports. Furthermore, the central focus is the intricate issue of zakāt distribution to non-Muslims under the al-Mu’allafah Qulūbuhum category, with particular emphasis on its applicability in modern contexts. The findings reveal that zakāt funds can be allocated to non-Muslims categorized as al-Mu’allafah Qulūbuhum for public interest (maṣlaḥah), specifically to foster interfaith relations and support da‛wah efforts either through tamlīk al-aʽyān (outright ownership) or tamlīk al-manfaʽah (beneficial ownership), whether mubāshir (direct) or ghayr mubāshir (indirect). This permissible allocation, supported by Sharī‛ah experts and some State Islamic Religious Councils (SIRCs), highlights an approach where zakāt's reach extends beyond direct Muslim beneficiaries under specific conditions to prevent discord, thereby exemplifying its holistic impact as a tool for socio-economic well-being. This study offers an evidence-based understanding of the distribution of zakāt to al-mu’allafah qulūbuhum in its contemporary Malaysian context, thereby contributing meaningfully to the academic discourse and practical policy development in zakāt management.